Facile and simple synthesis of silver‐doped hydroxyapatite porous microspheres with good sphericity. (20th April 2021) - Mei, Fengce; Yao, Shengkun; Xu, Wei‐li; Wu, Yanling; Wang, Yanmin; Qi, Mei‐li
Abstract: Silver‐doped hydroxyapatite (Ag‐HA) porous microspheres were synthesized by one‐step hydrothermal route at 180 °C for 10 h in the presence of l ‐glutamic acid (Glu) as a growth regulator. The effects of Glu concentration and silver ion doping on the phase and morphology of the products were thoroughly characterized by X‐ray diffraction and scanning electron microscopy. Results show that the presence of Glu induces the growth of hydroxyapatite crystals from flower‐like aggregates to porous microspheres, and the addition of silver ions can maintain the roundness of hydroxyapatite microspheres. The Brunauer–Emmett–Teller analysis, particle dispersity and antibacterial property were also conducted. The optimal parameters for porous silver‐doped hydroxyapatite microspheres with uniform morphology was obtained with the atomic molar ratio n (Ag)/ n [Ag + Ca] = 0.01 and Glu concentration at 0.06 M.